Designed formation of hollow particle-based nitrogen-doped carbon nanofibers for high-performance supercapacitors. Issue 8 (25th April 2017) - Chen, Li-Feng; Lu, Yan; Yu, Le; Lou, Xiong Wen (David)
Abstract : Hollow particle-based N-doped carbon nanofibers synthesized via a facile electrospinning and carbonization method exhibit enhanced supercapacitive performance. Abstract : Carbon-based materials, as one of the most important electrode materials for supercapacitors, have attracted tremendous attention. At present, it is highly desirable but remains challenging to prepare one-dimensional carbon complex hollow nanomaterials for further improving the performance of supercapacitors. Herein, we report an effective strategy for the synthesis of hollow particle-based nitrogen-doped carbon nanofibers (HPCNFs-N). By embedding ultrafine zeolitic imidazolate framework (ZIF-8) nanoparticles into electrospun polyacrylonitrile (PAN), the as-prepared composite nanofibers are carbonized into hierarchical porous nanofibers composed of interconnected nitrogen-doped carbon hollow nanoparticles. Owing to its unique structural feature and the desirable chemical composition, the derived HPCNFs-N material exhibits much enhanced electrochemical properties as an electrode material for supercapacitors with remarkable specific capacitance at various current densities, high energy/power density and long cycling stability over 10 000 cycles.